Engaged or distracted? Assessing medical students’ attention dynamics during lectures - Sohail, Hamnah; Noor, Tayyaba; Ismail, Laiba; Mohammad, Fatima; Aziz, Nauman (Journal of the Pakistan Medical Association, 2025)
Objective: To evaluate the concentration dynamics and assess the attention span of first year medical students. Method: The cross-sectional study was conducted at Sahiwal Medical College, Punjab, Pakistan, from October 8, 2023, to February 29, 2024, and comprised undergraduate first year medical students of either gender. The assessments were done during Physiology and Biochemistry classes that were taught by the respective head of department. The concentration of students was checked at 5-minute intervals during the entire lecture. Data was collected using a questionnaires were distributed among them after taking the informed consent. Data was analysed using SPSS 20. Results: Of the 107 students, 54(50.5%) were male and 53(49.5%) were female, 84(78.5%) were hostilities, and 87(81.3%) students had slept <8 hours on the preceding night. A total of 408 questionnaires were distributed during five different lectures, and the response rate was 100%. The concentration levels rose till the first 10 minutes after which they constantly declined till the end of the lecture except for a transient rise in concentration right at the end. The attention span of students during the Physiology lectures was significantly associated with gender, while that of the Biochemistry was significantly associated with sleep duration. Conclusion: Students’ concentration was at its peak during the initial 10 minutes and then drifted away during the rest of the lecture. Key Words: Lecture, Attention, Public sector, Undergraduate, Medical education, Vigilance, Cross-sectional study.